TFP and the Transmission of Shocks - Sebastian Rüth; Eric Mayer; Johann Scharler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We show that TFP reacts counter-cyclically to macroeconomic shocks, which we identify by imposing sign restrictions. Counterfactual simulations, based on a New Keynesian DSGE model, show that firms manage to employ labor more efficiently during downturns, which leads to a muted drop in the output gap as long as the recession is not deep enough to make the zero lower bound on the nominal interest rate binding. If the economy hits the zero lower bound, the reductions in both, employment and output gap, are stronger when we allow TFP to depend on the state of the business cycle.
Keywords: E32; E40; E50; 330